Examining the influence of social factors on Cambodian high school teachers’ self-efficacy and job performance - Sereyrath Em; Sarom Mok; Rany Sam (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
The current study aims to examine the influence of social factors on the self-efficacy and job performance of Cambodian high school teachers, with a particular emphasis on the differences between gender and age groups. To achieve this, a quantitative descriptive method and a causal-comparative analysis were used with data obtained from 639 high school teachers working in four provinces in Cambodia. Specifically, four important social aspects were investigated: the impact of colleagues, education policy, the income of teachers, and the socio-economic background of teachers. The findings indicate that all social determinants have a considerable impact on the self-efficacy and performance of teachers, with salary making the most important contribution. However, there were no statistically significant differences in teachers' perceptions across gender and age groups. This means that all the teachers need additional payments as a priority. Consequently, these findings bring to light the general significance of social effects on teachers' performance and emphasize the necessity of making systemic adjustments in teacher compensation, policy implementation, and support mechanisms. In brief, theoretical and practical implications for educational development in Cambodia are offered, contributing to the expanding body of literature on teachers’ living standards. Finally, future studies should employ a mixed-methods approach better to understand the same or different regions in the country.